2007
DOI: 10.1111/j.1365-2133.2007.08029.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in melanoma epidemiology suggest three different types of melanoma

Abstract: Temporal trends suggest the existence of three unrelated types of melanoma: type I, thick melanomas, with stable incidence; type II, thin melanoma with a steady and important increase in incidence, mainly located on the trunk; and type III, melanoma with a slower increase in incidence, mainly located on the head and neck region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 42 publications
10
87
2
5
Order By: Relevance
“…Annual incidence has risen as rapidly as 4-6% in many fair-skinned populations that predominate regions like North America, Northern Europe, Australia, and New Zealand (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Increases in incidence rates vary considerably across populations of different ethnicity and geographical location, and even within populations across age and gender (6,7,9,19,34,35).…”
Section: Incidencementioning
confidence: 99%
“…Annual incidence has risen as rapidly as 4-6% in many fair-skinned populations that predominate regions like North America, Northern Europe, Australia, and New Zealand (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Increases in incidence rates vary considerably across populations of different ethnicity and geographical location, and even within populations across age and gender (6,7,9,19,34,35).…”
Section: Incidencementioning
confidence: 99%
“…Although the mortality due to melanoma or malignant mutated pigment cell cancer has begun to stabilize in developed country (1,2), the disease shows, however a substantial increased incidence which, in term of public health, represents a high burden (3)(4)(5). As well known, among the risk factors leading to melanoma there is exposition to solar ultraviolet radiation associated to sensitive genetic background (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been questioned whether the increased disease surveillance programs have succeeded to identify melanomas with more indolent behavior (Swerlick and Chen, 1996), as it is shown that the incidence of biopsy rates between 1986 and 2001 was associated with an increase in diagnosis of in situ and local melanomas, but not the incidence of advanced melanomas, in nine geographical areas of the United States (Welch et al, 2005). More frequent thinner melanoma detection was also noted in Germany and France (Lasithiotakis et al, 2006;Lipsker et al, 2007). A large-scale prospective randomized survival-based study has not been carried out to prove benefit of skin cancer screening-although the requirement for such a study, or the ethics of being randomized to a non-screening arm, remains controversial.…”
Section: Trends In Melanoma Epidemiology Datamentioning
confidence: 99%